Urbanization of tourism areas in Phuket Island, Thailand: A case study of Patong, Kammala and Karon - Thinnukool,O. (Medwell Publishing, 2015)
© Medwell Journals, 2014. The factors influencing the urbanization growth of tourism industry have been debated and discussed by developers about tourism literature and the issue continues to be one of the most popular topics for research. Using Phuket tourism areas as the target population, researchers assessed areas such as Patong, Kamala and Karon. This study aims to review available approaches to model land-use change and thus identify priorities for future urbanization growth. A Logistic Regression Model was fitted separately to predict these outcomes since, 1975 to 2009 with those locations and the land-use 8 years earlier as determinants. The results of this study, therefore, do not only provide sufficient information on the urban growth in three places of Phuket tourism areas from 1967 to 2009 but they also provides quantitative information about urban change by simple geographical from freely available Software R Program. For the areas that had much than each locations, researchers found substantial changes in Patong, Kamala and Karon with 24.2, 13.0 and 19.5% of other land-use type, respectively, becoming urbanized while 93% of urban land did not change whereas the estimated urban growth of the island on the East-coast was higher than West-coast.